2021
DOI: 10.1371/journal.pcbi.1009543
|View full text |Cite
|
Sign up to set email alerts
|

From spikes to intercellular waves: Tuning intercellular calcium signaling dynamics modulates organ size control

Abstract: Information flow within and between cells depends significantly on calcium (Ca2+) signaling dynamics. However, the biophysical mechanisms that govern emergent patterns of Ca2+ signaling dynamics at the organ level remain elusive. Recent experimental studies in developing Drosophila wing imaginal discs demonstrate the emergence of four distinct patterns of Ca2+ activity: Ca2+ spikes, intercellular Ca2+ transients, tissue-level Ca2+ waves, and a global “fluttering” state. Here, we used a combination of computati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 78 publications
3
21
0
Order By: Relevance
“…Studies in Drosophila demonstrated intercellular Ca 2+ waves that traverse large tissue domains and might depend on actomyosin organization ( Balaji et al, 2017 ). These tissue-level Ca 2+ dynamics, which occur in imaginal discs, the tightly coupled epithelial structures that give rise to the external structures of the adult fly, were implicated in organ growth and size modulation ( Brodskiy et al, 2019 ; Soundarrajan et al, 2021 preprint). Furthermore, intercellular Ca 2+ waves were shown to be induced mechanically in these developing epithelia ( Narciso et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Drosophila demonstrated intercellular Ca 2+ waves that traverse large tissue domains and might depend on actomyosin organization ( Balaji et al, 2017 ). These tissue-level Ca 2+ dynamics, which occur in imaginal discs, the tightly coupled epithelial structures that give rise to the external structures of the adult fly, were implicated in organ growth and size modulation ( Brodskiy et al, 2019 ; Soundarrajan et al, 2021 preprint). Furthermore, intercellular Ca 2+ waves were shown to be induced mechanically in these developing epithelia ( Narciso et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, their model is implemented over a two-dimensional, homogenized continuum rather than over discrete cells in a tissue. A more recent model from the same lab investigates calcium signaling across a Drosophila wing disc, but with a focus on organ development and with the total IP 3 production rate in each cell being just a function of the cytosolic calcium concentration (Soundarrajan et al ., 2021). Donati et al (2021) developed a model of calcium signals in mouse keratinocytes upon photodamage; however, instead of proteolytic activation driving the extracellular signaling mechanism, the damage signal in that system is ATP, which is released both from the wound site as well as from undamaged cells through connexin hemichannels.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, their model is implemented over a two-dimensional, homogenized continuum rather than over discrete cells in a tissue. A more recent model from the same lab investigates calcium signaling across a Drosophila wing disc, but with a focus on organ development and with the total IP 3 production rate in each cell being just a function of the cytosolic calcium concentration (Soundarrajan et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted January 9, 2023. ; https://doi.org/10.1101/2023.01.08.523049 doi: bioRxiv preprint Previously, we have shown that perturbing Gαq expression regulates the size of Drosophila wings [46]. Further, we identified that the overexpression of wildtype Gαq is correlated with the occurrence of intercellular Ca 2+ waves (ICWs) in ex vivo wing disc cultures [46]. Further, Gαq is required for wound-induced Ca 2+ waves in the pupal notum [47], [48].…”
Section: Introductionmentioning
confidence: 99%